An Integrative Pan-Cancer Analysis of PBK in Human Tumors - Wen, Huantao; Chen, Zitao; Li, Min; Huang, Qiongzhen; Deng, Yuhao; Zheng, Jiawei; Xiong, Moliang; Wang, Pengfei; Zhang, Wangming (Frontiers in Molecular Biosciences, 2021)
Background: PDZ Binding Kinase (PBK), is a serine/threonine kinase, which belongs to the mitogen-activated protein kinase kinase (MAPKK) family. It has been shown as a critical gene in the regulation of mitosis and tumorigenesis, but the role of PBK in various cancers remain unclear. In this study, we systematically explored the prognostic and predictive value of PBK expression 33 cancer types. Methods: Public databases including cBioPortal database, GDSC database, GTEx database, CCLE database and TCGA database were used to detect the PBK expression, as well as its association with prognosis, clinicopathologic stage, TMB, MSI, immune microenvironment, immune checkpoints, immune cell infiltration, enrichment pathways and IC50 across pan-cancer. The statistical analyses and visualization were conducted by R software. Results: PBK expression is relatively high in most cancers compared to their normal counterparts, and barely express in normal tissues. High expression of PBK is significantly associated with poor prognosis and clinicopathologic stage I, II, III in different cancers. Furthermore, PBK expression strongly associated with TMB in 23 types of cancer and associated with MSI in 9 types of cancer. Moreover, the correlation analysis of microenvironment and immune cells indicated that PBK is negatively correlated with the immune infiltration levels, but positively correlated with the infiltration levels of M0, M1 macrophages, T cells CD4 memory activated and T cells follicular helper. GSEA analysis revealed that the biological function or pathways relevant to cell cycle and mitosis were frequently enriched in PBK high expression level. Conclusion: These results revealed the oncogenic role of PBK, which is significantly upregulated in various cancers and indicated poor prognosis and immune infiltration in multiple cancers. It also suggested that PBK may serve as a biomarker in multiple tumor progress and patients survival.